FROM ADMINISTRATIVE TO STRATEGIC: HOW HR CAN BECOME A TRUE BUSINESS PARTNER - Rizky Karnando Rachmat; Ramon Zamora; Dhenny Asmarazisa (RADJA PUBLIKA, 2026)
The evolution of the Human Resources function from an administrative to a strategic partner is critical for organizational success in the modern business landscape. Despite its recognized importance, a persistent gap exists between this strategic aspiration and the operational reality in many organizations, where HR remains focused on transactional tasks. This study aims to identify the key competencies, structural changes, and business acumen required for HR to transition into a genuine strategic business partner. Utilizing a qualitative multiple-case study methodology, data was collected through semi-structured interviews with senior HR leaders and C-suite executives across four multinational corporations. The results reveal that strategic HR partnership is predicated on three pillars: the mastery of data analytics for talent insights, the cultivation of deep business literacy, and a formalized seat at the strategic planning table. The discussion argues that this transition necessitates a fundamental redesign of HR roles and metrics, shifting from cost-centre efficiency to value creation and business impact. In conclusion, for HR to become a true business partner, it must transcend its administrative heritage by aligning talent strategy directly with core business objectives, thereby contributing to competitive advantage. This transformation is not merely functional but a strategic imperative for organizational resilience.